Digital Public Relations Content on the Facebook Pages of the Ministries of Defense and Interior - Shihab, Rasool Ahmed; Al-Shemary, Ali Jabar (ALBAHITH ALALAMI, 2025)
Objectives: This study aims to identify the content published on the digital Facebook pages of the Ministries of Interior and Defense, and their role in building the public image of security institutions, by analyzing the nature of messages provided by digital public relations. Methodology: The study used the survey method, which records, analyzes, and interprets a phenomenon by collecting comprehensive data. Content analysis was employed to examine the messages that contribute to shaping the public image, based on a comprehensive census of posts published by the two ministries between January 1, 2023, and March 31, 2023. A total of 360 posts were analyzed: 182 from the Ministry of Interior and 178 from the Ministry of Defense. Results: The findings showed that the published content focused on the performance of security institutions and the degree of their members’ commitment to the law, reflecting their discipline and diligence in carrying out their duties efficiently. Conclusion: The study confirmed that digital public relations for the Ministries of Interior and Defense contributed to enhancing the positive public image of security institutions by highlighting values of discipline and commitment to the law, thereby reinforcing public trust in these institutions.